Respuestas
Respuesta dada por:
21
Propiedades a usar
![log( {x}^{n} ) = n log(x) \\ log(a \times b) = log(a) + log(b) log( {x}^{n} ) = n log(x) \\ log(a \times b) = log(a) + log(b)](https://tex.z-dn.net/?f=+log%28+%7Bx%7D%5E%7Bn%7D+%29++%3D+n+log%28x%29++%5C%5C++log%28a+%5Ctimes+b%29++%3D++log%28a%29++%2B++log%28b%29+)
Entonces
![x = log(36) \\ x = log( {6}^{2} ) \\ x = 2 log(6) \\ x = 2( log(2 \times 3) ) \\ x = 2( log(2) + log(3) ) \\ x = 2(m + n) x = log(36) \\ x = log( {6}^{2} ) \\ x = 2 log(6) \\ x = 2( log(2 \times 3) ) \\ x = 2( log(2) + log(3) ) \\ x = 2(m + n)](https://tex.z-dn.net/?f=x+%3D++log%2836%29++%5C%5C+x+%3D++log%28+%7B6%7D%5E%7B2%7D+%29+++%5C%5C++x+%3D+2+log%286%29++%5C%5C+x+%3D+2%28+log%282+%5Ctimes+3%29+%29+%5C%5C+x+%3D+2%28+log%282%29++%2B++log%283%29+%29+%5C%5C+x+%3D+2%28m+%2B+n%29)
Entonces
Respuesta dada por:
12
Aplicando propiedades operacionales de otencis
36 = 2^2x3^2
log36 = x
= log(2^2x3^2)
= log2^2 + log3^2
= 2log2 + 2log3
= 2(m) + 2(n)
x = 2(m + n) respuesta
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años